2021
DOI: 10.7717/peerj.10879
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic stress in banana is relieved by exogenous nitric oxide

Abstract: Drought is one of the severe environmental stresses threatening agriculture around the globe. Nitric oxide plays diverse roles in plant growth and defensive responses. Despite a few studies supporting the role of nitric oxide in plants under drought responses, little is known about its pivotal molecular amendment in the regulation of stress signaling. In this study, a label-free nano-liquid chromatography-mass spectrometry approach was used to determine the effects of sodium nitroprusside (SNP) on polyethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 78 publications
(74 reference statements)
2
22
0
Order By: Relevance
“…The accumulation of excessive ROS can cause oxidative stress that leads to cell death and senescence. To survive, plants undergo a series of morphological, physiological, biochemical, cellular, and molecular changes [49]. Advances in omics and molecular technologies have identified signaling and regulatory pathways and characteristics of mechanisms underlying plant stress responses, providing valuable data in the information pool for crop improvement.…”
Section: Microbiome Engineering In Improving Abiotic Stress Tolerancementioning
confidence: 99%
“…The accumulation of excessive ROS can cause oxidative stress that leads to cell death and senescence. To survive, plants undergo a series of morphological, physiological, biochemical, cellular, and molecular changes [49]. Advances in omics and molecular technologies have identified signaling and regulatory pathways and characteristics of mechanisms underlying plant stress responses, providing valuable data in the information pool for crop improvement.…”
Section: Microbiome Engineering In Improving Abiotic Stress Tolerancementioning
confidence: 99%
“…Plants respond and adapt to drought stress conditions by changing regulatory circuits in transcription and protein expression, reorganizing metabolic pathways and physiological processes [16]. This is the first study to determine protein changes in response to drought stress in Pandanus using a TMT-labelled proteomics approach.…”
Section: Stress and Defense Protein Abundance Under Drought Stressmentioning
confidence: 99%
“…Goche et al reported that 237 and 187 root proteins were significantly altered in drought-susceptible and drought-tolerant sorghum varieties, respectively [12]. Other proteomics drought studies have also been reported on chickpea [13], grapevine [14], wheat [15], and banana [16].…”
Section: Introductionmentioning
confidence: 97%
“…As for osmotic stress, the supplement of SNP could alleviate over-accumulated ROS (reactive oxygen species)-caused oxidative damage as well as decrease the inhibition of root growth, chlorophyll content, and proline accumulation in osmotic stressed noa1 plants (Zhang et al, 2010 ). However, reducing NO accumulation by application of L-NAME leads to enhanced osmotic stress (Xing et al, 2004 ; Cao et al, 2019 ; Mohd Amnan et al, 2021 ). These findings show that NO can be induced when plants are subjected to various types of environmental stresses.…”
Section: Introductionmentioning
confidence: 99%